DA LIBERDADE DE PENSAR E SE MANIFESTAR E SEU CONTRAPONTO PELA CRIMINALIZAÇÃO DO DESACATO NO BRASIL: UMA ANALISE DA CONTITUCIONALIDADE E CONVENCIONALIDADE DO DELITO DE DESACATO NO ORDENAMENTO JURIDICO PÁTRIO. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This article seeks to analyze the typical figure of contempt in the Brazilian legal system and its controversies, in particular, it seeks to explore the reasons given by the Supreme Court for the maintenance of contempt as a typical criminal conduct, according to the content of the Habeas Corpus (HC) Judgment No. 141,949 - Federal District (DF); analyzing the compatibility of contempt with the Constitution of the Republic and with the set of international human rights treaties, to which Brazil is a signatory.Keywords: DISACTION. INTERNATIONAL TREATIES. HUMAN RIGHTS